Hill cattle of Pithoragarh district of Uttarakhand - PUNDIR, R K; SINGH, P K; SHARMA, D; SAINI, A; SINGH, C V; PRAKASH, B (The Indian Journal of Animal Sciences, 2012)
The Pithoragarh district had 2.23 lakh of cattle and 0.86 lakh buffaloes in 2003. Among the cattle there were 92.81% indigenous and most of them (more than 99%) were non- descript and need their characterization. A survey, including 82 farmers and 194 animals of different age and sex was conducted in 8 villages of Munsyari block of Pithoragarh district to characterize the hill cattle. The survey revealed that large number of hill cattle were available in the remote areas like in Munsyari block of the district and in surrounding areas there were large number of crossbred cattle mainly reared for milk production. In the surveyed area cattle were reared for milk, bullock power and manure. Animals were reared mainly on semi-intensive system of management i.e. grazing from morning to afternoon and thereafter stall feeding. In some villages there were no grazing, all the animals were stall fed. Animals were small in size with cylindrical-shaped body. Body colours vary in different colours i.e. brown, black and white or black & white. Tail was long touching to ground with black or white switch. The ranges of different biometric traits showed that animals were closer to Vechur and Punganaur breeds of cattle for their shape and size but smaller than the Hariana and Sahiwal breeds of cattle. The hill cattle available in Pithoragarh area were smaller in size as compared to hill cattle of Almora and bigger to that of cattle of Rudarprayag district. The average birth weight was 9.14 kg The average age at first calving, daily milk yield, lactation length, dry period, service period and calving interval were 40 months, 1.41 kg, 208 days, 138 days, 105 days and 485 days, respectively. Bullocks of the breed were used for 25–40 days in a year for different agricultural operations. A pair of bullock could plough about 6–8 Nali (0.4 acre) of land in a day.